Clinical efficacy of unilateral biportal endoscopic technique for adjacent segment pathology following lumbar fusion - Fei Feng; Guangpeng Li; Hai Meng; Hao Chen; Xiang Li; Qi Fei (Journal of Orthopaedic Surgery and Research)
Abstract Background Lumbar fusion surgery can lead to adjacent segment pathology (ASP). The unilateral biportal endoscopic (UBE) technique has been shown to be effective in treating lumbar degenerative diseases. However, few studies have evaluated its use for ASP. This single-center, retrospective study aimed to evaluate the short-term clinical efficacy and safety of the UBE technique for treating ASP following lumbar fusion. Methods A retrospective study was conducted involving 18 patients with ASP who met the established inclusion and exclusion criteria. All patients underwent the UBE technique and were followed for at least 6 months. In addition to UBE procedural parameters, patient-reported outcomes were assessed, including the Oswestry Disability Index (ODI), visual analog scale (VAS) scores for back and leg pain, Japanese Orthopaedic Association (JOA) scores, and the modified MacNab criteria, both preoperatively and at follow-up. Radiological assessments included the dural sac enlargement ratio, extent of bony decompression, and facet joints preservation rate. Results The mean follow-up duration was 15.94 months. Total blood loss averaged 273.03 ± 181.22 mL, and intraoperative hidden blood loss was 226.92 ± 178.12 mL. The mean operative time is 94.33 ± 27.09 min, and the average length of postoperative hospital stay was 3.56 ± 1.25 days. There were no neurological complications associated with the operation. The ODI, VAS scores for back and leg pain, and JOA scores improved significantly at the last follow-up, compared with preoperative values. Based on the modified Macnab criteria, 94.45% of patients reported excellent or good outcomes. Radiological evaluations showed no evidence of segmental instability at final follow-up. Conclusion The UBE technique achieves satisfactory short-term clinical outcomes in patients with ASP following lumbar fusion without exacerbating spinal instability. This approach may be particularly beneficial for elderly patients with multiple comorbidities who are less tolerant of additional fusion surgery. However, further research is needed to evaluate its long-term efficacy and safety.